"Asia is now the priority target for the world anti-tobacco movement": attempts by the tobacco industry to undermine the Asian anti-smoking movement. (24th November 2004) - Knight, J; Chapman, S
Abstract : Study objective: To identify and examine the strategies utilised by multinational tobacco companies to undermine and discredit key anti-tobacco activists and organisations in the Asian region. Method: A series of case studies drawing upon material gathered through systematic reviews of internal tobacco industry documents. Date sources: Tobacco industry documents made public as part of the settlement of the Minnesota Tobacco Trial and the Master Settlement Agreement. Results: The industry sought to identify, monitor, and isolate key individuals and organisations. The way industry went about fulfilling this mandate in the Asian region is discussed. Industry targetted individuals and agencies along with the region's primary anti-smoking coalition. Conclusions: Attack by multinational tobacco companies is a virtual quid pro quo for any individual or agency seriously challenging industry practices and policies. Understanding their tactics allows anticipatory strategies to be developed to minimise the effectiveness of these attacks.